Food technology to process plant-based food (soy protein isolate formula) - Made Astawan (World Nutrition Journal, 2020)
Soy protein isolate (SPI) is obtained by extracting the soluble protein and removing non-protein material such as fat and carbohydrates. Because of this process, it has a neutral flavor and cause less flatulence than soy flours. Furthermore, SPI has higher Protein Digestibility Corrected Amino Acid Score (PDCAAS) compared to soymilk, which is 100% and 92.6% respectively.